Psychosocial adjustment to skin conditions resulting in visible difference (disfigurement): What do we know? Why don't we know more? How shall we move forward? - N. Rumsey, PhD (Wolters Kluwer, 2018)
This article offers an overview of the current understanding of the psychological factors and processes that play a part in the continuum of distress and positive adjustment in people who are affected by dermatological conditions that affect appearance. Despite research demonstrating the significant psychosocial challenges posed by visible difference and mounting evidence of the role played by psychosocial variables in the etiology, exacerbation, and treatment of skin conditions, current healthcare provisions focus predominantly on the amelioration of physical manifestations. Impediments to progress in the understanding of psychological adjustment, blocks to the development of effective interventions, and challenges to the implementation of integrated psychological and medical care are reviewed. A route map to advance current understanding and care provision is proposed. Keywords: psychological adjustment, psychological intervention, health care provision